Kodivikasi variabel-variabel dalam penelitian ekonomi Islam - Suroso Imam Zadjuli (Universitas Islam Indonesia, 1998)
It is needed a special analysis tool to develop Islamic economics. This article state that we can borrow conventional economics tools to read and analysis Al Quran and Hadits related with economics, so it will be obtained general principles of Islamic economics.